Application of a hybrid virtual-physical teaching model integrating mixed reality and 3D printing in clinical joint orthopedic education - Wang, Honglin; Xu, Aoshuang; Hua, Wei; Ye, Zhewei; Lu, Lin (Frontiers in Surgery, 2025)
ObjectiveThe diagnosis and treatment of arthropathic orthopaedic conditions are inherently linked to anatomical structures, necessitating strong spatial visualization abilities in students. Providing intuitively accessible methods for students to master specialized knowledge presents a formidable challenge for educators. This study aims to evaluate the pedagogical value of integrating 3D-printed model with mixed reality (MR) technology in clinical orthopaedic surgery education.MethodsThirty-six senior clinical medical undergraduates were randomized into two groups. The experimental group underwent training using the combined 3D- printed model and mixed reality (MR) technology, while the control group received traditional instruction. Learning outcomes were evaluated through standardized Objective Structured Clinical Examination (OSCE) assessments and questionnaires. Correlation analysis was conducted between total OSCE scores and questionnaire scores.ResultsThe experimental group achieved significantly higher OSCE scores compared to the control group (p < 0.05). Questionnaire analysis indicated that a majority of students in the experimental group perceived the integrated 3D printing and mixed reality (MR) teaching approach as innovative. They also reported significant improvements in anatomical comprehension, interest stimulation, teacher-student interaction, knowledge retention, learning efficiency, and practical skills (p < 0.05). Furthermore, OSCE total scores demonstrated strong positive correlations with all questionnaire subdomains (r > 0.8, p < 0.001). The strongest correlation was observed between learning efficiency and OSCE total scores (r = 0.918).ConclusionIntegrating 3D-printed model and MR technology into orthopedic joint surgery clinical teaching significantly boosts student performance, learning efficiency, and overall teaching quality, demonstrating strong potential for wider application.